Analisis Pengelolaan Keuangan (Studi Analisis Target Costing Dalam Meningkatkan Laba Pada Kaka Cake Jambi) - Desi Melawati; As'ad Isma; Ahmad Syahrizal (Pusat Riset dan Inovasi Nasional, 2023)
This research is entitled Financial Management Analysis (Target Costing Analysis Study in Increasing Profit at Kaka Cake Jambi City). The research method used by the researcher is a qualitative approach. The results of this study are: (1) Business management of Kaka Cake Jambi broadly consists of product management, price, marketing and business income details of Kaka Cake Jambi. In terms of products, most of the products produced by Kaka Cake Jambi are dessert boxes with 20 flavors. The price of Jambi's Kaka Cake products ranges from Rp.29,000 - Rp.38,000. Meanwhile, the promotion carried out by Kaka Cake Jambi is through social media such as Facebook, Instagram and marketplace where the wider community will be able to find products easily. In one month, Mrs. Yolanda's income from this Kaka Cake business reaches approximately 200 million per month, with a monthly profit of 40 million to 60 million per month. (2) The target costing method applied to the making of the Jambi Cake Kaka Dessert Box in determining the selling price of the dessert box, Kaka Cake applies the pricing principle by looking at the market price and the purchasing power of consumers to determine the selling price of the dessert box. At this stage of determining the profit target, Kaka Cake Jambi is targeting a profit of approximately 100% of production costs. Kaka Cake targets a profit of Rp.10,000 to Rp.20,000 for each variant of the dessert box produced. With this profit target, Kaka Cake Jambi must determine the target cost in accordance with the profit target to be obtained. While the maximum cost target that needs to be spent by Kaka Cake Jambi for the Dessert Box variant of Cheese Krunchy is Rp. 10,000, Kaka Cake can minimize costs so that profits are maximized or more than Rp. 19,000. (3) The target costing method applied by Kaka Cake in the production of dessert boxes is quite effective in obtaining an optimal level of profit. It is said to be quite effective because the profits obtained do not reach 100% of production costs as targeted for profit targets, this is due to the labor costs that must be incurred by Kaka Cake Jambi of Rp.17,200,000 per month for 9 employees.